Synthesis of 1,3-Azol-2-yl O-Heterocycles by Microwave-Irradiation-Assisted Direct C–H Functionalization - Sipos, Zoltán; Kónya, Krisztina (Synlett, 2018)
A microwave-irradiation-assisted synthesis of novel 1,3-azol-2-yl-substituted O-heterocycles, namely flavones, chromones, coumarins, and chromanones, is reported. Starting from the appropriate bromo derivatives and 1,3-azoles, this palladium and copper co-catalyzed method provides moderate to good yields and excellent regioselectivity. The ligand- and base-free method can be a useful, generally applicable synthetic tool in the formation of new O-heterocycles.
Keywords: O-heterocycles; azoles; palladium catalysis; copper catalysis; arylation; microwave heating